A comparative study of linear and nonlinear mass damping systems under seismic excitation. (15th September 2020) - Tsiatas, George C.; Charalampakis, Aristotelis E.; Tsopelas, Panos
Highlights: Seismic mitigation of linear and nonlinear mass damping systems is studied. An artificial seismic motion and a set of 20 real ground motions are employed. The artificially excitation consistently underestimates critical design quantities. The nonlinear systems result in greater variability as compared to the linear ones. Abstract: A comparative study of the seismic response of structures equipped with linear and nonlinear mass damping systems is presented herein. Three optimized mass damping systems mounted at the top of a linearly elastic two-degree-of-freedom building are tested under an artificial seismic motion to assess their response. The artificial seismic motion is generated using the SIMQKE software and matching a specific response spectrum. The mass damping systems consist of (i) a Linear Mass Damper (LMD), (ii) a type-I Nonlinear Energy Sink (NES) with a nonlinear elastic spring of the cubic oscillator, and (iii) a Friction Nonlinear Energy Sink (FNES) which extends the NES with a friction element and a linear elastic spring of potentially negative stiffness. The results for each configuration are validated with a set of real scaled ground motion time histories matching the same specific spectrum, and a quantification of the response variability in relation to the input variability is attempted. An interesting observation is that the artificially generated excitation consistently underestimates critical design/response quantities, as compared to the average response of the set of real ground motions.